Intercalated Electrolyte with High Transference Number for Dendrite‐Free Solid‐State Lithium Batteries - Chen, Long; Li, Wenxin; Fan, Li‐Zhen; Nan, Ce‐Wen; Zhang, Qiang (Advanced functional materials, 2019)
Solid‐state lithium (Li) batteries using solid electrolytes and Li anodes are highly desirable because of their high energy densities and intrinsic safety. However, low ambient‐temperature conductivity and poor interface compatibility of solid electrolytes as well as Li dendrite formation cause large polarization and poor cycling stability. Herein, a high transference number intercalated composite solid electrolyte (CSE) is prepared by the combination of a solution‐casting and hot‐pressing method using layered lithium montmorillonite, poly(ethylene carbonate), lithium bis(fluorosulfonyl)imide, high‐voltage fluoroethylene carbonate additive, and poly(tetrafluoroethylene) binder. The electrolyte presents high ionic conductivity (3.5 × 10−4 S cm−1), a wide electrochemical window (4.6 V vs Li+/Li), and high ionic transference number (0.83) at 25 °C. In addition, a 3D Li anode is also fabricated via a facile thermal infusion strategy. The synergistic effect of high transference number intercalated electrolyte and 3D Li anode is more favorable to suppress Li dendrites in a working battery. The solid‐state batteries based on LiFePO4 (Al2O3 @ LiNi0.5Co0.2Mn0.3O2), CSE, and 3D Li deliver admirable cycling stability with discharge capacity 145.9 mAh g−1 (150.7 mAh g−1) and capacity retention 91.9% after 200 cycles at 0.5 C (92.0% after 100 cycles at 0.2 C) at 25 °C. This work affords a splendid strategy for high‐performance solid‐state battery. The intercalated composite solid electrolyte presents a large ionic conductivity and high ionic transference number. The synergistic effect of the high transference number intercalated electrolytes and 3D lithium anode effectively suppresses lithium dendrites. The assembled batteries deliver a high cycling performance, demonstrating a promising strategy for ambient‐temperature solid‐state lithium metal batteries.